RATIONALE FOR TRANSLATION PROJECT MANAGEMENT COURSE AS ACADEMIC DISCIPLINE - Perminova, Alla (Advanced Education, 2018)
The article provides for the rationale for a Translation Project Management course as an academic discipline that is designed to meet translation majors’ needs and facilitate their entry into the profession. Its tapestry methodology incorporates current trends in contemporary Translation Studies with an emphasis on interdisciplinarity, internationalism, technological advances, student-empowerment, collaborative professional realism, and an outcomes-based approach. The theoretical strands are devised to show how students can benefit from incorporating into their professional portfolio project management techniques and quality control processes. The practical strands provide for student-empowerment in their work on real translation projects. The article sheds light into the progress made by the students throughout the period of instruction, activities in which they were involved, challenges they faced while working on their translation projects, and the results of the course evaluation by students themselves on the basis of an introspective analysis of the applicability of acquired knowledge and skills, as well as appraisal made by external examiners invited to the presentation of the students’ projects. As a result of successful implementation, the course has become an integral part of the educational and research programme for training MA graduate students specialising in Philology.